PENINGKATAN KINERJA SUMBER DAYA MANUSIA DALAM KONTEKS TEKNOLOGI INFORMASI - Ken Sudarti (Value Added : Majalah Ekonomi dan Bisnis, 2016)
This research aims to describe and analyze the social capital variables, intellectual capital, and the performance of human resources in the context of information technology as well as to arrange a model of the role of information technology in moderating equation the performance of human resources. Employees used a population that is in the secretariat of the council representatives of  Buton Regions that totaled 75 people. The sample is taken with  census approach, the overall population  as respondents research so that the total sample in this research is 75 people. The analysis instrument structural equation is modeling (SEM) withPartial Least Square (PLS 2.0 M3) method. The research results show that the social capital has a positive influence on human resources and intellectual capital. In addition intellectual capital also has a positive influence on the human resources performance. Information technology as variable moderation couldn’t give a moderating effect to equation in improving  human resources performance as submitted by researchers .Keyword: Social capital, Intelectual capital, information technology, performance of human resource